Assessing the Dynamics of Corporate Value in the Textile and Garment Industry: The Role of Company Size, Asset Growth, and Public Ownership Structure - Bakti, Hudi Setyo; Lyundira, Fetri Setyo; Safari, Dedy Eko Trisyono; Dewi, Intan Tri (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2025)
Assessment of a company's condition of performance, often assessed based on stock price. The better the value of a company, the more attractive the stock is by investors. In obtaining maximum profits and small risks, investors need to look at the aspects that affect the value of the Company, especially in the textile industry which is experiencing the dynamics of global economic changes. This study aims to determine the influence of company size, asset growth, and public ownership structure on company value. Sampling was conducted by purposive sampling, with a total of 20 companies in the textile and garment industry sector on the IDX. Data analysis using multiple linear regression analysis with the SPSS application tool version 26. The test results obtained a determination coefficient (R²) of 0.279 or 27.9%, while the company size coefficient was -0.309 with a significance of 0.000, asset growth of 3.555 with a significance of 0.000 and public ownership of -0.118 with a significance of 0.802. The conclusion obtained is that the size of the company has a negative effect and the growth of assets has a positive effect on the value company, while the structure of public ownership has no effect on the value of the company.